Stakeholder Groups of Public and Private Universities in the Czech Republic – Identification, Categorization and Prioritization - Marie Slabá (Review of Economic Perspectives, 2015)
With regard to changes in the environment of tertiary education and tertiary educational systems, universities are now unlikely to succeed as `separated closed' institutions that are unresponsive to their environment and stakeholders. Stakeholder analysis is considered as an important part of university management and marketing and universities have to take care of key stakeholder groups and build long term relationships with them. This paper focuses on the stakeholder analysis and adopts the stake-holder theory and analysis for the needs of the Czech market of tertiary education. This paper analyses results of the author's online questionnaire that provided the input for data analysis deploying basic descriptive analysis and first steps of stakeholder analysis – identification, categorization and prioritization. Results of author's research show that there are only slight differences between public and private universities and their perspective concerning generic stakeholder groups of universities. However the research revealed two controversial stakeholder groups – donors and competitors. In comparison with other stakeholder groups perception of these two stakeholder groups by public and private universities is very different. Stakeholder groups of public and private universities were categorized into four basic groups - primary internal stakeholder groups, primary external stakeholder groups, secondary internal stakeholder groups, and secondary external stakeholder groups. Primary internal and external stakeholder groups which are crucial for survival of universities are the most important stakeholder groups for universities. The author identified ten most important stakeholder groups for public and private universities separately, based on assigned priorities that will be used for further research.
Keywords: 330